Mood indigo [videorecording (DVD)] - Gondry, Michel; Tautou, Audrey, 1976-; Duris, Romain, 1974-; Elmaleh, Gad; Vian, Boris, 1920-1959 (Drafthouse Films (Series), 2014)
A love story set in a charmingly surreal Paris about two newlyweds, Chloé and Colin, whose whirlwind courtship is tested when an unusual illness plagues Chloé : a flower begins to grow in her lungs.